Exploring the multi-function nature of packaging in the food industry - Ageliki Konstantoglou; Dimitris Folinas; Thomas Fotiadis (Logistics, 2020)
The main objective of this paper is the identification and evaluation of packaging elements by the involved managers in the food industry. Primary research data was collected using a questionnaire that was completed by marketing and logistics managers, as well as food technologists and executives assigned to environmental initiatives/practices, in the Greek food industry. The findings reveal that different managers have different perceptions regarding packaging shapes, colors, identification coding schemes and the provision of consumption ways. There are some common packaging elements that most managers agree on, which are: providing nutritional information, including marks that show compliance to environmental practices, being easy to transport and handle, and withstanding corrosion and wear. Moreover, the research confirms that: (a) Health and nutrition are two interrelated concepts that receive constant attention from the food industry, as well as from governments and consumers, and (b) The quality of a food product is inextricably linked to the quality of its packaging.
Keywords: 650; food supply chain; Greece; holistic approach; packaging elements; survey